Analysis of Farmers' Understanding and Compliance in Paying Agricultural Zakat in Tebedak Village, Ogan Ilir - Melis Melis; Hikmah Endraswati; Annisa Astrid (Jurnal I-Philanthropy, 2023)
This article aims to analyze the extent to which farmers in Tebedak Village pay agricultural zakat. The method used in this writing is field research, employing a qualitative approach. The study involved 10 farmers as respondents from Tebedak Village, Ogan Ilir. Data collection techniques included observation, interviews, and documentation. Direct observation was conducted to observe problems and phenomena within the community, particularly among farmers in Tebedak Village, Ogan Ilir District. The study revealed that the majority of farmers in Tebedak Village, Ogan Ilir Regency, had a limited understanding of agricultural zakat due to insufficient knowledge and a lack of socialization from institutions, the government, and village officials regarding various types of zakat maal. Farmers often mistake zakat for infaq and alms, and consider zakat maal as a voluntary act that may or may not be paid. Furthermore, the level of compliance among farmers in paying zakat is not fully satisfactory, as revealed through interviews with the respondents. This can be attributed to their ignorance and lack of awareness about the obligation to pay agricultural zakat.